Spatial distribution and policy implications of the exhaust emissions of two-stroke motorcycle taxis: a case study of southwestern state in Nigeria - P. K. Alimo; G. Lartey-Young; S. Agyeman; T. Y. Akintunde; E. Kyere-Gyeabour; F. Krampah; A. Awomuti; O. Oderinde; A. O. Agbeja; O. G. Afolabi (Journal of Nigerian Society of Physical Sciences, 2024)
Two-stroke motorcycles emit harmful exhaust fumes because of incomplete combustion. Although they constitute the main fleet of motorcycle taxis in sub-Saharan Africa, monitoring, spatial assessment, and regulation are weak, leaving dire health consequences in cities. This study collected motorcycle raw exhaust emissions of 1,950 two-stroke petrol-driven motorcycle taxis, otherwise called okada, in Ogun State, Nigeria, using an idle mode test approach under 10 minutes and employed correlations, hierarchical multiple linear regression models, and spatial analysis. It was found that carbon monoxide (CO) and hydrocarbons (HC) were the most highly concentrated, and the latter were beyond allowable limits. The concentration of CO was found to be at the minimum of 0.00 % and the highest being at 6.40% (an average of 1.05%), while the HC concentration was reported at the minimum of 18.00 ppm and the highest at 15446 ppm (an average of 3560 ppm). Notably, Kriging interpolation analysis indicated that cumulative effects due to the clustering and operations of motorcycle taxis could increase these concentrations over time, extending their long-term impacts. Given the severe effects of these emissions on health and the wider environment, a DPSIR policy framework is proposed to regulate two-stroke motorcycle taxis in sub-Saharan Africa.